1988
DOI: 10.1039/c39880000156
|View full text |Cite
|
Sign up to set email alerts
|

Antibody labelling with functionalised cyclam macrocycles

Abstract: Functionalised 'cyclam' macrocyclic ligands have been selectively attached t o thiol residues on a monoclonal antibody and form kinetically inert complexes with Cup+ and TcV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…In addition, the availability of 62 Zn- 62 Cu generators and 64 Cu with high specific activity makes it more feasible to develop target-specific radiopharmaceuticals with copper radionuclide. Copper radionuclide production, coordination chemistry, radiochemistry, and nuclear medicine applications have been reviewed exhaustively [6,7,13,72,[224][225][226][227][228].…”
Section: Why Copper Radionuclides?mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the availability of 62 Zn- 62 Cu generators and 64 Cu with high specific activity makes it more feasible to develop target-specific radiopharmaceuticals with copper radionuclide. Copper radionuclide production, coordination chemistry, radiochemistry, and nuclear medicine applications have been reviewed exhaustively [6,7,13,72,[224][225][226][227][228].…”
Section: Why Copper Radionuclides?mentioning
confidence: 99%
“…Because of the d 9 configuration, Cu(II) complexes are often kinetically labile with respect to ligand dissociation. Therefore, the design of BFCs (Figure 11) for copper radionuclides has been focused on macrocyclic chelators that are able to form Cu(II) complexes with both high thermodynamic stability and kinetic inertness [224][225][226][227][228]. BFCs for radiolabeling of biomolecules with copper radionuclide have been reviewed recently [225].…”
Section: Copper Chemistrymentioning
confidence: 99%
“…Numerous chelators have been reported for complexing copper [5][6][7][8][9][10][11][12][13][14][15][16] and several of these have been functionalized to allow attachment to antibodies [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and are now commercially available. The choice of antibody/BFC combination will affect efficacy as an imaging or therapy agent.…”
Section: Introductionmentioning
confidence: 99%
“…Such macrocycles have been made by a variety of methods, including high-dilution techniques [2] and routes based on template effects [3]. The groups of Kimura [4] and Morphy [5] reported that, consistent with earlier findings of Tabushi et al [6], neither high-dilution nor templates are required for the condensation of diesters with a,w-diamines to form macrocyclic diamides. Later, we found that this reaction can even be carried out at room temperature [7] and that various diesters, as long as they possess a heteroatom in a-position to the CO group, are efficient substrates [8 ± 11].…”
mentioning
confidence: 60%